Pharmacological prevention of serious anaphylactic reactions due to iodinated contrast media: systematic review. Issue 7570 (31st July 2006) - Tramèr, Martin R; von Elm, Erik; Loubeyre, Pierre; Hauser, Conrad
Abstract: Objective To review the efficacy of pharmacological prevention of serious reactions to iodinated contrast media. Design Systematic review. Data sources Systematic search (multiple databases, bibliographies, all languages, to October 2005) for randomised comparisons of pretreatment with placebo or no treatment (control) in patients receiving iodinated contrast media. Review methods Trial quality was assessed by all investigators. Information on trial design, population, interventions, and outcomes was abstracted by one investigator and cross checked by the others. Data were combined by using Peto odds ratios with 95% confidence intervals. Results Nine trials (1975-96, 10 011 adults) tested H1 antihistamines, corticosteroids, and an H1 -H2 combination. No trial included exclusively patients with a history of allergic reactions. Many outcomes were not allergy related, and only a few were potentially life threatening. No reports on death, cardiopulmonary resuscitation, irreversible neurological deficit, or prolonged hospital stays were found. In two trials, 3/778 (0.4%) patients who received oral methylprednisolone 2×32 mg or intravenous prednisolone 250 mg had laryngeal oedema compared with 11/769 (1.4%) controls (odds ratio 0.31, 95% confidence interval 0.11 to 0.88). In two trials, 7/3093 (0.2%) patients who received oral methylprednisolone 2×32 mg had a composite outcome (including shock, bronchospasm, and laryngospasm) compared with 20/2178 (0.9%) controls (odds ratio 0.28, 0.13 to 0.60). In one trial, 1/196 (0.5%) patients who received intravenous clemastine 0.03 mg/kg and cimetidine 2-5 mg/kg had angio-oedema compared with 8/194 (4.1%) controls (odds ratio 0.20, 0.05 to 0.76). Conclusions Life threatening anaphylactic reactions due to iodinated contrast media are rare. In unselected patients, the usefulness of premedication is doubtful, as a large number of patients need to receive premedication to prevent one potentially serious reaction. Data supporting the use of premedication in patients with a history of allergic reactions are lacking. Physicians who are dealing with these patients should not rely on the efficacy of premedication.